2017
DOI: 10.3389/fneur.2017.00579
|View full text |Cite
|
Sign up to set email alerts
|

Novel Anterior Brainstem Magnetic Resonance Imaging Findings in Non-Small Cell Lung Cancer with Leptomeningeal Carcinomatosis

Abstract: Leptomeningeal carcinomatosis (LC) is found in around 4% of patients with non-small cell lung cancer (NSCLC). The most common radiological finding of LC is diffuse leptomeningeal enhancement on contrast-enhanced brain magnetic resonance imaging (MRI). Herein, we report a novel brain MRI finding—non-enhanced, band-like, symmetric restricted diffusion along the anterior surface of the brainstem—of LC in four patients with NSCLC. We also identified three additional cases with similar MRI findings in a literature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 9 publications
2
18
0
Order By: Relevance
“…However, in up to 25% of lung cancer cases, the chest X-ray does not reveal any abnormal lesions and returns a perfect “normal” diagnosis. If you still suspect cancer, you can also use other more sensitive diagnostic methods, including computed tomography (CT) or MRI scans [ 3 , 4 ]. According to the results, the doctor may wish to obtain a lung tissue sample by using a puncture to confirm.…”
Section: Introductionmentioning
confidence: 99%
“…However, in up to 25% of lung cancer cases, the chest X-ray does not reveal any abnormal lesions and returns a perfect “normal” diagnosis. If you still suspect cancer, you can also use other more sensitive diagnostic methods, including computed tomography (CT) or MRI scans [ 3 , 4 ]. According to the results, the doctor may wish to obtain a lung tissue sample by using a puncture to confirm.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, novel magnetic resonance imaging (MRI) findings in leptomeningeal carcinomatosis due to lung adenocarcinoma have been reported (1,2). Case 1 was a 55-year-old man presenting with dizziness and vomiting.…”
mentioning
confidence: 99%
“…His MRI findings (Picture 2) were similar to those in Case 1. Although it is hypothesized that malignant cells infiltrate into the perforating arteries along the brainstem surface and cause microinfarctions (2), there is no pathological evidence supporting this notion.…”
mentioning
confidence: 99%
“…We hypothesize that T2 abnormalities without enhancement could also be considered a response determination in LC according to some circumstances, even if it has a false-positive possibility. Similarly, Cheng et al (6) also reported that follow-up brain MRI showed persistent hyperintensity on fluid-attenuated inversion recovery, imaging, and restricted diffusion of the anterior brainstem lesions after IT chemotherapy. Although the proposal for response evaluation remains controversial because of its complexity, we support the view that a complete cerebrospinal MRI should be routinely repeated to evaluate response to treatment.…”
Section: Discussionmentioning
confidence: 79%
“…The etiology and pathogenesis of this phenomenon remain unclear. Some researchers have hypothesized that malignant cells in the subarachnoid cisterns infiltrate the perforating arteries along the brainstem surface and cause microinfarctions (5,6). Because of microvascular obstruction and insufficient collateral circulation, it is difficult for gadolinium to reach the brainstem lesions and so the lesions are usually not enhanced.…”
Section: Discussionmentioning
confidence: 99%